Pelatihan Kepemimpinan melalui Loyalitas Organisasi dalam Mengakselerasi Kapasitas Kepemimpinan Pengurus OSIS Pah Tsung School Jakarta - Ali Wardhana; Ellen Sandria (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The leadership of student organizations (OSIS) is often confined to formal and technical aspects, creating a gap in emotional intelligence development and increasing the risk of unhealthy organizational dynamics such as groupthink and blind loyalty. This community service program aimed to strengthen the leadership capacity of OSIS members at Pah Tsung School, Tangerang, Banten, Indonesia, through the cultivation of organizational loyalty integrated with human values and empathy. The program involved 29 participants, consisting of 28 OSIS student members and 1 OSIS advisor teacher. A participatory training approach was employed through four main stages: needs identification, module development incorporating case studies, interactive workshops, and comprehensive evaluation. The results demonstrated a significant improvement in participants’ understanding of healthy organizational loyalty and empathy-based leadership. Evaluation data from 28 student participants showed a high level of program effectiveness, with an average score of 3.4 out of 4.0. Participants particularly appreciated the clarity of material delivery (3.50) and its relevance to real organizational challenges (3.46). Beyond increasing knowledge, the program produced practical outcomes in the form of enhanced critical thinking, greater awareness of the importance of balancing organizational commitment with empathy, and the establishment of a more humane student leadership framework. This initiative contributes to the development of student leaders who are not only organizationally responsible but also emotionally intelligent and capable of fostering healthy organizational cultures.